The Effect of New Breaching in a Prudhoe Bay Causeway on the Coastal Distribution of Humpback Whitefish - Fechhelm, Robert G. (ARCTIC, 1999)
West Dock is a solid-gravel petroleum production causeway 4.3 km long that was constructed along the Beaufort Sea coast near Prudhoe Bay, Alaska, in the late 1970s. In the winter of 1995-96, a breach 200 m wide was constructed 1 km from the base of the causeway. Fish monitoring studies conducted during the summers of 1996 and 1997 indicated that the catch of adult (>= 200 mm fork length) humpback whitefish (Coregonus pidschian) had increased significantly east of West Dock relative to levels observed in the 11 previous years. Data suggest that humpback whitefish dispersing eastward along the coast from their overwintering grounds in the Colville River had been blocked from moving east of West Dock and that construction of the breach has allowed these fish to extend their summer foraging range farther to the east. West Dock est un pont-jetée de 4,3 km de long, construit avec du gravier, en structure pleine. Il a été édifié le long du rivage de la mer de Beaufort, près de Prudhoe Bay en Alaska, à la fin des années 70, en vue de la production pétrolière. Durant l'hiver de 1995-1996, une brèche de 200 m a été ouverte à 1 km du point d'attache du pont-jetée. Des travaux de surveillance du poisson menés durant les étés de 1996 et 1997 ont révélé que les prises de cisco à bosse (Coregonus pidschian) adulte (>= 200 mm de longueur à la fourche) avaient augmenté de façon notable à l'est de West Dock par rapport aux niveaux relevés au cours des 11 années précédentes. Les données suggèrent que le cisco à bosse, qui longe la côte en direction de l'est depuis son aire d'hivernage dans la rivière Colville, avait la route bloquée pour aller à l'est de West Dock et que la construction de la brèche lui avait permis d'étendre plus à l'est son aire estivale d'alimentation.